BUILDING STUDENT CHARACTER THROUGH DA’WAH JOURNALISM: AN IMPORTANT ROLE AT STIT ISLAMIYAH KARYA PEMBANGUNAN PARON NGAWI - Sugiharto, Sugiharto (PT. Hafasy Dwi Nawasena, 2025)
This study examines the role of da'wah journalism in building the character of students at STIT Islamiyah Karya Pembangunan Paron Ngawi. The formation of student character in the Islamic education environment requires a holistic approach that integrates Islamic values in the learning process. Da'wah journalism as an Islamic communication medium has great potential in instilling character values such as honesty, discipline, responsibility, tolerance, and social concern. This study uses a qualitative method with a descriptive-analytical approach to analyze the implementation of da'wah journalism in the formation of student character. The results of the study show that the integration of da'wah journalism in the Islamic higher education curriculum can be an effective strategy to build the character of students who are moderate, religious, and with integrity. Practice-based learning methodologies, the use of digital technology, and adequate supervision are key to the success of this program. The research recommends the need for a curriculum revision that integrates prophetic values in journalistic competence as well as the development of comprehensive assessment methods to measure character formation quantitatively and qualitatively.